2013
DOI: 10.1038/onc.2012.633
|View full text |Cite
|
Sign up to set email alerts
|

ISGylation governs the oncogenic function of Ki-Ras in breast cancer

Abstract: Aberrant expression of the oncogenic Kirsten-Ras (Ki-Ras) and interferon-stimulated gene 15 (ISG15) pathways is common in breast and other cancers. However, whether these dysregulated pathways cooperate to promote malignancy is not known. This study links Ki-Ras and ISG15 in a previously unidentified regulatory loop that may underlie malignant transformation of mammary cells. We show that oncogenic Ki-Ras regulates the expression of the ISG15 pathway (free ISG15 and ISG15 conjugates), and ISG15, in turn, stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 51 publications
6
88
1
Order By: Relevance
“…2A). Of the 19 ISGs detected, we focused on ISG15 as a gene of potential interest as it encodes for a protein that can function intracellularly to modify cytoplasmic and nuclear proteins, it can also be secreted from activated cells as free ISG15, and ISG15 has been shown to play a putative role in other solid tumors such as bladder, oral, prostate, and breast cancers (19)(20)(21)(22)(23)(24). We confirmed the microarray results by RTqPCR and Western blot analysis.…”
Section: Macrophages Increase the Expression And Secretion Of Isg15 Wsupporting
confidence: 60%
See 2 more Smart Citations
“…2A). Of the 19 ISGs detected, we focused on ISG15 as a gene of potential interest as it encodes for a protein that can function intracellularly to modify cytoplasmic and nuclear proteins, it can also be secreted from activated cells as free ISG15, and ISG15 has been shown to play a putative role in other solid tumors such as bladder, oral, prostate, and breast cancers (19)(20)(21)(22)(23)(24). We confirmed the microarray results by RTqPCR and Western blot analysis.…”
Section: Macrophages Increase the Expression And Secretion Of Isg15 Wsupporting
confidence: 60%
“…This apparent overexpression was not all that surprising as Kras-transformed tumors have been shown to overexpress IFNb (38), a strong inducer of ISG15, and our IFNb ELISA and VSV anti-viral assays both confirmed that PDAC cells produce soluble and biologically active IFNb. Interestingly, a growing body of evidence over the past few years has shown a link between ISG15 and tumorigenesis for several solid tumors (19)(20)(21)(22)(23)(24). The general conclusion from these studies is that ISG15 is overexpressed in many tumor cell lines and ISGylation is important for malignant transformation; however, the mechanism(s) by which ISG15 exerts its protumor effects and whether ISG15 functions the same in all solid cancer entities is still unknown.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In vitro cell line-based studies have revealed contrary roles for protein ISGylation in tumorigenesis (27)(28)(29). However, these conclusions depend largely on cell-autonomous events, such as cell proliferation, cell death, and cell evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Protein ISGylation is strongly enhanced upon pathogen infection and cellular stress related o IFN induction (25). Several in vitro studies using cell lines and human cancer samples have begun to reveal anti-and protumorigenic roles of ISGylation (27)(28)(29). However, in vivo studies of protein ISGylation in tumorigenesis are relatively rare and have become a pressing need for understanding the role of ISG15 in malignant progression.…”
mentioning
confidence: 99%